Solar wind‐driven geopotential height anomalies originate in the Antarctic lower troposphere. Issue 18 (22nd September 2014) - Lam, Mai Mai; Chisham, Gareth; Freeman, Mervyn P.
Abstract We use National Centers for Environmental Prediction/National Center for Atmospheric Research reanalysis data to estimate the altitude and time lag dependence of the correlation between the interplanetary magnetic field component, By, and the geopotential height anomaly above Antarctica. The correlation is most statistically significant within the troposphere. The peak in the correlation occurs at greater time lags at the tropopause (∼6–8 days) and in the midtroposphere (∼4 days) than in the lower troposphere (∼1 day). This supports a mechanism involving the action of the global atmospheric electric circuit, modified by variations in the solar wind, on lower tropospheric clouds. The increase in time lag with increasing altitude is consistent with the upward propagation by conventional atmospheric processes of the solar wind‐induced variability in the lower troposphere. This is in contrast to the downward propagation of atmospheric effects to the lower troposphere from the stratosphere due to solar variability‐driven mechanisms involving ultraviolet radiation or energetic particle precipitation.